Walt Whitman's New Orleans : Sidewalk Sketches and Newspaper Rambles - Whitman, Walt, 1819-1892 (Book collections on Project MUSE., 2022)
"Scholars and biographers often mention Walt Whitman's short stint in New Orleans-three months in the spring of 1848-as a crucial moment of literary and personal development, with some of the author's most celebrated poems showing distinct influences of the city. Working for the local newspaper the Daily Crescent, the poet who was still seven years away from publishing the first edition of his Leaves of Grass would spend his afternoons, as he did in New York, strolling through the multiracial city to absorb and then write about his impressions. While Whitman's southern sojourn has become a core component of the narrative around the poet, his actual writings produced in the Crescent City have remained relatively obscure. Walt Whitman's New Orleans is the first book to collect his writings about the city, appearing more than 150 years after his trip south. Edited by Whitman expert Stefan Schöberlein, the volume builds on cutting-edge research that uncovers a previously unknown collection of short prose sketches that Whitman wrote for the Crescent after he left New Orleans. The result is a volume of humorous glimpses of city life steeped in the tropes and attitudes of the 1840s. These short pieces form a collage of impressions by a 'pedestrian,' as Whitman identifies himself in one piece, who provides interested readers with what he variously called 'Peeps,' 'Sketches,' or 'Glimpses' culled from his visits to the French Quarter, the St. Louis Hotel, Lafayette Square, and other central locales. Organized around the complete run of a humorous series titled 'Sketches of the Sidewalks and Levee,' Walt Whitman's New Orleans pairs his writings with nineteenth-century illustrations that capture views of the city and caricatures of the characters that populate his prose renderings. The volume also offers new discoveries about the Crescent staff and contextual information about the social, political, and cultural currents circulating throughout antebellum New Orleans, including their impact on Whitman's own evolving beliefs"--